Influence of linear and angular parameters on lower third molar retention: the role of space allocation and transpalatal width - Contreras-Madrid, Ana Isabel; Melwani-Sadhwani, Roshan; Velázquez-Cayón, Rocío Trinidad; Pérez-Jorge, David; Cassol Spanemberg, Juliana (Frontiers in Oral Health, 2025)
BackgroundThe mandibular third molars are the most frequently impacted teeth, followed by their maxillary counterparts and the upper canines. Their retention is influenced by several anatomical and developmental factors, including limited retromolar space, unfavorable angulation, and eruption trajectory—each critical for proper emergence.ObjectiveThis study examines the association between the eruption or impaction of mandibular third molars and variables such as eruption space, transpalatal width, and eruption angulation.Materials and methodsSeventy-one mandibular third molars were evaluated using 31 jaw models and 31 orthopantomograms (OPGs). Transpalatal width was measured linearly on the models, while angular data concerning eruption space and direction were derived from the OPGs. Statistical analysis was performed using SPSS (v.25).ResultsRetention was observed in 12.9% of cases. Linear assessments indicated that 51% of the molars were at risk of impaction, contingent on their angulation.ConclusionsMaxillary constriction significantly increases the risk of mandibular third molar retention. Linear measurements proved more reliable than angular metrics in estimating eruption space. Thus, for diagnosing transverse maxillary discrepancies, linear transpalatal width measurements are preferred over non-metric evaluations.